2005
DOI: 10.1111/j.1440-1827.2004.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of 14‐3‐3 sigma protein in human urological and gynecological tumors using a multi‐tumor microarray analysis

Abstract: 14-3-3 sigma is an exclusive epithelial marker and data on its expression in different malignancies are very scarce. The aims of the present study are to screen its expression in the most common neoplasms occurring in the urological and gynecological tract and to evaluate its use as a diagnostic marker. A tissue microarray was constructed using 350 samples from 13 different neoplasms. Immunohistochemical analysis using a polyclonal 14-3-3 sigma antibody was performed. Overall, this protein was positive in 141 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, Mhawech et al (15) identified low level of 14-3-3Û protein in 3/9 (33%) cervical SSCs, whereas, Sano et al (30) did not find low level of 14-3-3Û protein in any of the 29 cervical SSCs tested. In the present study we detected low level of 14-3-3Û in about 50% of cervical SSCs when comparing with normal cervical squamous epithelium.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, Mhawech et al (15) identified low level of 14-3-3Û protein in 3/9 (33%) cervical SSCs, whereas, Sano et al (30) did not find low level of 14-3-3Û protein in any of the 29 cervical SSCs tested. In the present study we detected low level of 14-3-3Û in about 50% of cervical SSCs when comparing with normal cervical squamous epithelium.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study we detected low level of 14-3-3Û in about 50% of cervical SSCs when comparing with normal cervical squamous epithelium. These conflicting results may be explained by the small number of cases included in the previous works (15,30), the use of different 14-3-3Û antibodies and immunohistochemical staining methods and the differences in scoring of the immunohistochemical staining. The low 14-3-3Û protein level in a relative high number of cervical SSC and the finding of no association between 14-3-3Û protein expression and FIGO stage, suggested that loss of 14-3-3Û protein expression may occur as a relatively early event in cervical tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In lung cancer, one report showed that squamous cell carcinomas express 14-3-3σ more strongly than adenocarcinomas, suggesting that this protein has a tendency to be more expressed in cells with squamous differentiation [62]. As an epithelial marker, 14-3-3σ expression could distinguish prostatic adenocarcinoma from urothelial carcinoma and seminoma from embryonal carcinoma [68]. This finding may help pathologists to differentiate these tumor types.…”
Section: -3-3 In Cell Spreading and Migrationmentioning
confidence: 93%
“…Alterations in the expression of 14-3-3σ were shown to be characteristic for distinct cell types in tumors of the same location. For example, 14-3-3σ expression was used to distinguish various types of ovarian carcinoma [35], and to discriminate between urothelial and prostate carcinoma [36].…”
Section: Silencing Of 14-3-3σ σ σ σ σ In Cancermentioning
confidence: 99%